Assessing the Effect of Interactivity Design In VR Based Second Language Learning Tool - Harris, Christene; Sun, Bo (2022 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2022)
Virtual Reality (VR), as a helpful tool in language education, is widely supported by the current literature. VR can provide a variety of stimulating scenarios that keep learner engagement high so its use in the language classroom has increased rapidly. This makes it necessary for further research to be conducted in the field to determine ways to maximize its potential. This research aims to determine if the level of interactivity presented in an Immersive VR Environment is a factor that will impact a user's capability to successfully learn a second language, particularly when facing subjects with different age, gender, and previous VR experience. To satisfy these aims, 3 versions of a Virtual Reality Language Learning Application were created with varying levels of interactivity. Participants of this study were administered pre and post evaluations to analyze the efficiency of their second language learning experience. Our results show that the level of interactivity may not be a factor that impacts a user's capability of learning and provide insight into the factors needed for successful language learning in Virtual Reality.